Proteomic analysis of the herpes simplex virus 1 virion protein 16 transactivator protein in infected cells. Issue 12 (29th April 2015) - Suk, Hyung; Knipe, David M.; Cristea, Ileana M.; Graham, David
<x xml:space="preserve">Abstract</x> The herpes simplex virus 1 virion protein 16 (VP16) tegument protein forms a transactivation complex with the cellular proteins host cell factor 1 (HCF‐1) and octamer‐binding transcription factor 1 (Oct‐1) upon entry into the host cell. VP16 has also been shown to interact with a number of virion tegument proteins and viral glycoprotein H to promote viral assembly, but no comprehensive study of the VP16 proteome has been performed at early times postinfection. We therefore performed a proteomic analysis of VP16‐interacting proteins at 3 h postinfection. We confirmed the interaction of VP16 with HCF‐1 and a large number of cellular Mediator complex proteins, but most surprisingly, we found that the major viral protein associating with VP16 is the infected cell protein 4 (ICP4) immediate‐early (IE) transactivator protein. These results raise the potential for a new function for VP16 in associating with the IE ICP4 and playing a role in transactivation of early and late gene expression, in addition to its well‐documented function in transactivation of IE gene expression.